Emotional Self-Knowledge - Montes Sánchez, Alba; Salice, Alessandro (Taylor & Francis, 2023)
Alba Montes Sánchez, Alessandro Salice, emotional self-knowledge, self-knowledge, emotions, affectivity, philosophy of emotion, self-discovery, social identity, responsibility, Indian philosophy, self-esteem, narrative self-understanding, Alba Montes Sánchez, Alessandro Salice, emotional self-knowledge, self-knowledge, emotions, affectivity, philosophy of emotion, self-discovery, social identity, responsibility, Indian philosophy, self-esteem, narrative self-understanding, boredom, introspection, self-consciousness, group-based emotions, hostile emotions